The Beneficial Effects of Traditional Chinese Exercises for Adults with Low Back Pain: A Meta-Analysis of Randomized Controlled Trials - Zhang, Yanjie (Medicina (Kaunas), 2019)
Objective: The aim of this meta-analytic review was to quantitatively examine the effects of traditional Chinese exercises (TCE) on pain intensity and back disability in individuals with low back pain (LBP). Methods: Potential articles were retrieved using seven electronic databases (Medline, Embase, Cinahl, Web of Science, Cochrane library, China National Knowledge Infrastructure, and Wanfang). The searched period was from inception to 1 March 2019. Randomized controlled trials (RCTs) assessing the effect of TCE on pain intensity and back disability in LBP patients were included. Pooled effect sizes were calculated using the random-effects models and 95% confidence interval (95% CI). Results: Data from eleven RCTs (886 individuals with LBP) meeting the inclusion criteria were extracted for meta-analysis. Compared with the control intervention, TCE induced significant improvements in the visual analogue scale (VAS) (Hedge’s g = −0.64, 95% CI −0.90 to −0.37, p < 0.001), Roland–Morris Disability Questionnaire (RMDQ) (Hedge’s g = −0.41, 95% CI −0.79 to −0.03, p = 0.03), Oswestry Disability Index (ODI) (Hedge’s g = −0.96, 95% CI −1.42 to −0.50, p < 0.001), and cognitive function (Hedge’s g = −0.62, 95% CI −0.85 to −0.39, p < 0.001). In a meta-regression analysis, age (β = 0.01, p = 0.02) and total exercise time (β = −0.0002, p = 0.01) were associated with changes in the VAS scores, respectively. Moderator analyses demonstrated that Tai Chi practice (Hedge’s g = −0.87, 95% CI −1.38 to −0.36, p < 0.001) and Qigong (Hedge’s g = −0.54, 95% CI −0.86 to −0.23, p < 0.001) reduced VAS scores. Interventions with a frequency of 1–2 times/week (Hedge’s g = −0.53, 95% CI −0.98 to −0.07, p = 0.02) and 3–4 times/week (Hedge’s g = −0.78, 95% CI −1.15 to −0.42, p < 0.001) were associated with reduced VAS scores, but this significant reduction on this outcome was not observed in the weekly training frequency of ≥5 times (Hedge’s g = −0.54, 95% CI −1.16 to 0.08, p = 0.09). Conclusions: TCE may have beneficial effects for reducing pain intensity for individuals with LBP, regardless of their pain status.